Peran Pondok Pesantren dalam Meningkatkan Religiusitas Masyarakat Studi Kasus Pondok Pesantren Al-Kahfi Randusari dan Pondok Qur’an Alima - Ihsan Faizal; Hakimuddin Salim; Mohammad Zakki Azani (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the role of Islamic boarding schools in increasing community religiosity, with case studies at Al-Kahfi Randusari Islamic Boarding School and Alima Balong Qur'an Boarding School. The purpose of this study is to describe the strategy and impact of pesantren activities on the improvement of religious values in the surrounding community. This study uses a qualitative descriptive approach, with data collection techniques in the form of observation, in-depth interviews, and documentation. The subjects of the study include pesantren leaders, ustadz, students, and the community in the pesantren environment. The results of the study show that the two pesantren have an important role in shaping the religious character of the community through non-formal education, habituation of daily worship such as congregational prayers and tadarus, and strengthening morals and spiritual values. In addition, various socio-religious activities such as public recitation, social services, and Islamic-based skills training have also increased the active participation of the community in religious life. These efforts have proven effective in strengthening individual and collective religious behavior, building harmonious social relationships, and fostering a strong Islamic character in society. However, this study also found a number of obstacles, including limited human and material resources, as well as challenges in inviting the community to follow guidance consistently. The implications of these findings show the importance of close collaboration between Islamic boarding schools, community leaders, and related agencies to strengthen inclusive and adaptive da'wah to social dynamics. Thus, pesantren not only function as a religious education institution, but also as a center for sustainable community development and oriented towards the formation of noble morals.